Will Following the Regulatory Script for GMOs Promote Public Acceptance of Gene-Edited Crops?. Issue 12 (December 2019) - Herman, Rod A.; Fedorova, Maria; Storer, Nicholas P.
Abstract : Risk-disproportionate regulation of gene-edited crops has been proposed to gain public acceptance for this breeding technique. However, confounding safety regulations with advocacy for an underlying technology risks weakening achievement of both objectives. Dedicated factual communication and education from trusted sources is likely to better support public acceptance of gene-edited crops.